Exam grading 2021: The challenges ahead. (2nd May 2021) - Middlehurst, Tom
Abstract : Several trends are emerging from the concerns that school leaders have about this summer's exam grading process. Tom Middlehurst looks at the main sticking points and offers advice and reassurance for secondary school leaders and teachers